Shade Tree Selection in Cocoa Agroforestry: Ghanaian Farmers' Preferences, Ecological Insight and Drivers of Local Ecological Knowledge - Michael Asigbaase; Solomon Batamia Ndego; Belinda Effah (Ecology and Evolution)
ABSTRACT Integrating shade trees into cocoa farms potentially reduces the environmental cost of cocoa production and enhances their conservation value. However, it is unclear how farmers' shade trees preferences vary across cocoa production stage and how these preferences influence biodiversity conservation outcomes, including tree species at risk. Therefore, grounded in the Social‐Ecological Systems framework, we collected data from 363 cocoa farmers via questionnaire‐led interviews and farmer responses regarding shade tree preferences and knowledge using linear mixed‐effects models, cluster analysis, and mean rating scores. The results showed that farmers' local ecological knowledge was primarily influenced by membership in farmer‐based organizations, number of information sources, credit access frequency, and cocoa production stage. Farmers cited 23 preferred shade tree species, indicating a moderate pool of preferred shade tree species among cocoa farmers. Albizia ferruginea and Newbouldia laevis were uniquely preferred by farmers with young cocoa farms while Senna siamea was unique to old cocoa farmers. Jaccard dissimilarity indices indicated that species composition became increasingly distinct as cocoa plantations aged (27.3% dissimilarity in younger farms vs. 65% in older farms), yet overall shade tree diversity remained stable. Overall, 40%–57% of preferred shade trees required conservation priority based on International Union for Conservation of Nature Red List and national star rating. It was concluded that socio‐economic factors including information access, and institutional support mediate conservation‐oriented behavior in agroforestry landscapes and that the composition of farmers' preferred shade tree species changes as the plantation ages, but with a stable diversity. These findings suggest that integrating farmers' preferred shade trees on cocoa farms has a potential tree species conservation value. The study extends Social‐Ecological Systems applications by highlighting how system components interact to influence conservation behavior. Investigating the long‐term impacts of shade tree diversity on cocoa agroforestry farms is critical to enhance their integration and cocoa productivity.